Astronomy in the Divine Comedy - Risaliti, Guido (Il Colle di Galileo, 2023)
There are over a hundred astronomical passages in the Divine Comedy. Astronomy is used both for its symbolic value and for its “exactness” in determining the times and places of the story. In order to appreciate, understand and value this aspect of the poem, the reader has to be able to identify with an intellectual of Dante’s time, amazed and fascinated by the explanatory and predictive capacity of the Ptolemaic system, in a pre-scientific era in which the understanding of natural phenomena was extremely limited.